Out Of Pocket (OOP) Health Expenditure and Utilization of Financial Risk Protection Measures Among COVID-19 Affected Individuals in Chennai- A Cross-Sectional Study - Swetha NB; Angeline Grace; Sujitha P; Umadevi R (Medsci Publications, 2022)
Background: Pandemic has affected people physically, mentally and economically. India being a growing economic power house, spends only around 1.2% of GDP on health which thereby leads to high OOP spending. This study aims to estimate out of pocket health expenditure and proportion of financial risk protection. Methods: Cross sectional study conducted among Covid-19 affected individuals in Chennai. It was a questionnaire based study with questions about covid-19 management status, cost and insurance utilization. Descriptive statistics and regression analysis was used for analysis. Results: Total of 47 were treated at hospital and 85% of them were treated at private hospital.. The mean cost investigations for patients treated at hospital was of Rs. 50000+11547 and for medicines was Rs. 110000+57735. 53% of study participants had health insurance. 29 (54.72%) of them had Covid-19 treatment cost covered under insurance. The multiple regression analysis showed a statistically significant association between total OOPE incurred and age, religion and socio-economic status. Conclusion: Majority of participants spent for their treatment through savings and borrowing money. OOPE was compensated by reimbursement through health insurance. Provision of quality health care in government hospitals, increase public health spending and creating awareness about health insurance are ways to reduce OOP costs.